Effects of volleyball plyometric intervention program on vertical jumping ability in male volleyball players - Mroczek, D.; Mackala, K.; Kawczynski, A.; Superlak, E.; Chmura, P.; Seweryniak, T.; Chmura, J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study aimed to investigate the effect of a 6-week plyometric exercise training program on the development of lower limb explosive power in terms of vertical jumping ability in university level volleyball players. The study involved 9 male volleyball players from the AWF Wroclaw University Sports Club, with a minimum of 5 years of training and competition experience. The program consisted of various bounds, hops, and jumps in vertical, horizontal, and mixed directions. During the program, a progressive overload of plyometric intervention was applied. Lower limb explosive power in the form of vertical jumping ability was developed and tested. METHODS: The jumping ability was evaluated via 5 types of maximum-effort vertical jumps, using the Opto Jump system. In addition, once each week, the heart rate was recorded using a heart rate monitor (Polar RS300X GPS). RESULTS: The only significant correlation was found between squat jump and number of jumps and between counter movement jump and heart rate. CONCLUSIONS: From a practical standpoint, the improvement, which was noticed after 3 and 6 weeks, seems to optimal period for volleyball players adaptation to significant increased training load.